Proceedings of the 7th International Driving Symposium on Human Factors in Driver Assessment, Training, and Vehicle Design : Dr 2013
DOI: 10.17077/drivingassessment.1538
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Assessment of Perceived and Objectively Scaled Workload of a Voice-Based Driver Interface

Abstract: Summary:Interaction with a voice-command interface for radio control, destination entry, MP3 song selection, and phone dialing was assessed along with traditional manual radio control and a multi-level audio-verbal calibration task (nback) on-road in 60 drivers. Subjective workload, compensatory behavior, and physiological indices of cognitive workload suggest that there may be both potential benefits and cautions in the implementation of a representative production level interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 11 publications
1
19
1
Order By: Relevance
“…In some cases, the system will brake automatically when cross-traffic is detected (see e.g., Seto et al 2012). A US study in Massachusetts investigated the effects of a cross-traffic alert system in response to real vehicle encroachment with 42 drivers (one-third of whom were age 61–68) (Reimer et al 2010). The study found that when compared to not using the system, participants experienced slightly but not significantly lower stress levels as measured by changes in heart rate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In some cases, the system will brake automatically when cross-traffic is detected (see e.g., Seto et al 2012). A US study in Massachusetts investigated the effects of a cross-traffic alert system in response to real vehicle encroachment with 42 drivers (one-third of whom were age 61–68) (Reimer et al 2010). The study found that when compared to not using the system, participants experienced slightly but not significantly lower stress levels as measured by changes in heart rate.…”
Section: Resultsmentioning
confidence: 99%
“…Studies testing these types of systems in real-world settings with middle-age and older drivers have found that use of the system: reduced mental workload when parking (Tachibana 2011; Totzke et al 2010); reduced stress as measured by a reduction in heart rate (Reimer et al 2010); improved parking behavior as measured by a number of factors (Reimer et al 2010; Totzke et al 2011); rated more positively and might transfer learning so that parking will be improved even when the system is not being used (Reimer et al 2010; Totzke et al 2011; Kawabata et al 2008). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Training began with manual phone contact calling, followed by voice phone contact calling and then by voice destination address entry. For the embedded vehicle systems, following the approach taken in Reimer, Mehler, McAnulty, et al (2013) and Mehler et al (2014), the default factory-setting configurations for the vehicle voice interfaces were used, and participants were given guidance on the use of short-cut command options to reduce the number of steps required to complete tasks. As an example of a short-cut, to use the voice interface in the Sensus system, calls could be placed by first saying the command ‘Phone’, waiting for a response and saying ‘Call Contact’.…”
Section: Methodsmentioning
confidence: 99%
“…Concerns have been raised about the cognitive demands of tasks that still remain with voice interfaces (Cooper, Ingebretsen, and Strayer 2014; Reimer, Mehler, McAnulty, et al 2013; Reimer et al 2010, 2012; Strayer et al 2013; Strayer 2015a, 2015b; Strayer et al 2014). At the same time, several studies have found that self-reported workload, physiological arousal (e.g.…”
Section: Introductionmentioning
confidence: 99%